SOSIALISASI PENYULUHAN HUKUM PERATURAN PEMERINTAH NOMOR 39 TAHUN 2021 TENTANG JAMINAN PRODUK HALAL PERUM WIDOROSARI KARTOSURO SUKOHARJO JAWA TENGAH - Solikhah, Solikhah; Burhanudin, Burhanudin; Jamin, Mohammad; Mayastuti, Anti; Sulistiyaningsih, Nur; Hastuti, Luthfiyah Trini; Purwadi, Hari; Mulyanto, Mulyanto; Supbrowati, Gayatri Dyah; Rianto, Agus; Luthfiyah, Zeny; Gumbira, Seno Wibowo (Nindikayla Institute, 2023)
The general public's low understanding of basic provisions related to halal is still very low in general and this includes Perum Widorosari, Kartosuro District, Sukoharjo Regency, Central Java. So it is necessary to socialize legal counseling Government Regulation Number 39 of 2021 concerning Guarantees of Halal Products and various technical provisions for its application to be very appropriate and relevant to continue to be carried out. Public understanding that is adequate for the importance of implementing halal standards will pave the way for the establishment of halal zones that specifically fulfill the consumer's needs